Can a School-Based Intervention Improve the Oral Health-Related Quality of Life of Brazilian Children?. (July 2019) - Tomazoni, F.; Vettore, M.V.; Baker, S.R.; Ardenghi, T.M.
Introduction: Evidence of the effectiveness of oral health promotion strategies among children from different socioeconomic backgrounds is necessary to support the implementation of public health interventions. Objectives: This study aimed to test the effectiveness of a school-based intervention to enhance the sense of coherence (SOC) and oral health-related quality of life (OHRQoL) of socially vulnerable Brazilian children. Furthermore, we explored the pathways by which the intervention may improve OHRQoL and SOC, assessing the direct and indirect pathways among demographic, clinical, socioeconomic, behavioral, and psychosocial variables. Methods: In this cluster-randomized trial, 5 primary schools in Brazil were randomly allocated into intervention and control groups. The intervention comprised 7 sessions of SOC-based activities over 2 mo, which focused on making the school environment a place to develop children's SOC through involving teachers, school staff, and children. Trained teachers delivered the intervention. OHRQoL and SOC data were collected at baseline, 2 wk after the intervention, and at 3-mo follow-up. Results: Information about oral clinical conditions, socioeconomic status, OHRQoL, and SOC was obtained from 356 children aged 8 to 14 y (165 in the intervention group and 191 in the control group). Children from the SOC-based intervention group reported fewer impacts of their oral health on their daily lives (Child Perceptions Questionnaire mean, 7.22) than those from the control group (9.14). The intervention group also reported greater improvement of SOC at 2 wk (SOC mean, 52.98) and 3 mo (52.75) than the control group (52.21 and 51.65, respectively). Conclusion: The intervention was effective in improving SOC and OHRQoL among socially vulnerable Brazilian children. Moreover, SOC was a relevant predictor for oral symptom and functional status in this population (Brazilian Clinical Trials Registry RBR-2N9NHJ). Knowledge Transfer Statement: Clinicians and policy makers can use the results of this study to decide which approach to use when planning public health policy to improve the SOC and OHRQoL of socially vulnerable children. Our findings can assist policy makers in making more appropriate community health decisions in school environments that will improve community empowerment.